MATHEMATICS MODEL OF THE EFFECTS OF SARS-COV-2 MUTATIONS ON THE COVID-19 SPREADING IN A REGION - PUJI RAHAYU, IRA
Coronavirus disease (COVID-19) caused by the Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2) virus has become a global widespread pandemic since it was first identified in Wuhan City in December 2019. Over time, various types of SARS-CoV-2 variants have emerged because of viral mutations that cause changes in the characteristics of the virus, such as how quickly it spreads and the severity of the disease. In this study, a mathematical model of the spread of COVID-19 will be discussed by considering two conditions. The first is the wild- type model when the virus variant has not yet emerged or only the original virus has spread in a population. The second is a mutant-type model when there is a mutant strain that spreads in a population with the original virus. Then, we will look at the effects of non-pharmaceutical interventions on the COVID-19 spreading to control the spread of infection. Based on the numerical results, it was found that the spread of COVID-19 was higher due to the presence of a more infectious mutant strain or a higher transmission rate. However, the existence of the non-pharmaceutical interventions can reduce the rate of the COVID-19 spreading. Besides, an estimation of model parameters will also be carried out based on data from COVID-19 cases in Indonesia using cases of the Delta and Omicron variants as case studies.